(untitled) - Humphreys, J. F. (Cambridge, UK, 2004)
This thoroughly revised and updated version of the popular textbook on abstract algebra introduces students to easily understood problems and concepts. John Humphreys and Mike Prest include many examples and exercises throughout the book to make it more appealing to students and instructors.
Keywords: Group theory,Number theory,Lý thuyết nhóm,Lý thuyết số